2022
DOI: 10.3390/su14105764
|View full text |Cite
|
Sign up to set email alerts
|

A Review of On-Site Carwash Wastewater Treatment

Abstract: In recent years, people’s environmental awareness has increased. The high density of the urban population has caused a considerable increase in the demand for car washing services, which has created large quantities of car wash wastewater. The main pollutants in car wash wastewater are detergents, dirt, oil, and grease. Untreated wastewater released into rainwater sewer systems or other water bodies may pollute the water and generate excessive bubble foams, which negatively affects urban appearance. Car washes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Obviously, water recovered from wastewater must meet the required quality criteria for reuse [ 2 , 11 , 12 , 13 , 14 ]. For instance, suspensions may be effectively removed from wastewater by several methods, such as coagulation, sedimentation, adsorption and sand filtration [ 3 , 7 , 15 , 16 , 17 , 18 , 19 ]. It is necessary to point out that car wash wastewaters also contain significant amounts of pathogenic microorganisms [ 20 , 21 , 22 ]; hence, ensuring biosecurity is another key challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, water recovered from wastewater must meet the required quality criteria for reuse [ 2 , 11 , 12 , 13 , 14 ]. For instance, suspensions may be effectively removed from wastewater by several methods, such as coagulation, sedimentation, adsorption and sand filtration [ 3 , 7 , 15 , 16 , 17 , 18 , 19 ]. It is necessary to point out that car wash wastewaters also contain significant amounts of pathogenic microorganisms [ 20 , 21 , 22 ]; hence, ensuring biosecurity is another key challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth underlining that these compounds have high toxicity and contain numerous toxic metals such as arsenic, barium, cadmium, chromium, lead, iron, nickel, silver, sulfates, COD, BOD, nitrites, nitrates, E. coli, oils and greases, MBAS, among others, which, when discharged into receiving bodies without proper treatment, cause eutrophication, toxicity to aquatic species, undermine the oxygenation of the environment, and all this, associated with other potential effects, make the disposal of this type of effluent a major contributor to environmental pollution, and the volumes discharged annually are too significant to be ignored by environmental agencies. 28,30,41,43 Currently, in Chapeco, for example, the only treatment process for effluents from car wash stations are boxes (SAO, as per its Portuguese acronym), which are concrete boxes, built at ground level, containing three sections with dividing walls through which the effluent is transported, retaining the coarse solids and OGs before the effluent is disposed of in streams or in the sewage collection system of the city. Still, at the scientific research level, there are studies conducted in the past decade that, as introduced and thoroughly discussed, 256 employed biological systems, chemical coagulation/flocculation systems, membrane separators, advanced oxidative processes, EC processes, and some inter-combinations for the treatment of vehicle wash station effluents (VWSE).…”
Section: Recent Applications Of This Technology To the Car Wash Waste...mentioning
confidence: 99%
“…Therefore, the treatment of these effluents has become an eminent need on a global scale. 28,29 Was reported that 30 by 2020, there were estimated to be 1.5 billion vehicles on the planet; and, if they were washed just once a month, 1.8 billion tons of wastewater would be generated from the water used in these operations, enough to serve 33 million people and costing $1.8 billion annually. The authors highlight that this volume represents the total consumption of the population of Malaysia, Venezuela, the Republic of Ghana, Oceania (including Australia and New Zealand), or the combined population of Denmark, Norway, Switzerland, Finland, and Iceland.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations